Implementasi Kebijakan Program Komando Strategis Pembangunan Pertanian (Kostratani) di Kecamatan Sukodono Kabupaten Sidoarjo - Dyas Syahlia Izmi; Mahmudalia Rosa Yulaicho; Ertien Rining Nawangsari (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The Agricultural Development Strategic Command Program (Kostratani) emerged as the government's effort to realize national food sovereignty. Sidoarjo Regency, which has an area of 71,424.3 km2 and an area of 23,566 hectares of rice fields, with the agricultural sector being a leading commodity, seeks to realize the objectives of the program through the District Agricultural Extension Center (BPP), one of which is in Sukodono. The purpose of this study is to determine the extent of the implementation of the Strategic Agricultural Development Command Program (Kostratani) in Sukodono District, Sidoarjo Regency. This research uses descriptive qualitative research methods with data collection techniques through interviews with related parties and data observation. The theory used in this study is the theory of policy implementation from Merilee S.Grindle. The results of this study are expected to provide knowledge of public administration related to agriculture, especially the Strategic Agricultural Development Command Program (Kostratani). In addition, it is hoped that this research can help farmers to further increase agricultural potential and the urgency of agricultural progress in supporting the realization of national food sovereignty.